Sistem Penunjang Keputusan Pemilihan Mahasiswa Berprestasi Menggunakan Metode Profile Matching - Rika Sintia Kolatlena; Welly Angela Riry (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2022)
Introduction: The development of information technology today requires fast and accurate information in its implementation. Selection of outstanding students with the support of a decision support system is one of the implementations of the development of information technology.Purposes of the Research: applying the Profile Matching method as a method to solve multi-criteria problems by making system designs and designing decision support software.Methods of the Research: The method used in writing this paper is literature study and observation. Types of data and primary data collection through interviews and secondary data through library research.Result of the Research: The results showed that uses the profile matching method on this decision support system produces an application for a decision support system for selecting outstanding students that can be used in higher education. The criteria used in the decision support system to select outstanding students are: the value of scientific work, extracurricular activities, English language skills and personality. The results of this study are to produce a ranking order of prospective outstanding students who have been selected, and the output of the application can assist decision makers in choosing alternative students who excel. The application in this research is implemented using visual basic programming language, and database using Microsoft Access 2007.